266 Evaluation of peri-partum supplementation of methionine hydroxy analog on cow-calf performance. (7th December 2018) - Redifer, C; Tucker, H; Loy, D; Gunn, P
Abstract: The objective was to evaluate the effects of peripartum supplementation of methionine hydroxy analog (MFP ® ; Novus International) to beef cows on cow and calf performance. Primiparous Angus cows (n=60) were blocked by expected parturition date, stratified by BCS and BW, and randomized to 1 of 15 pens (4 cows/pen). Pens were randomly assigned to 1 of 3 dietary treatments; basal diet supplemented with 0, 15, or 30 g/hd/d MFP ® . The diet consisted of ground hay, silage, and distillers grains and was formulated to maintain similar BW across treatments. Diets were fed from 45 ± 13 d before calving through 74 ± 13 d postpartum when all cow-calf pairs were commingled and managed as a group until weaning (199 ± 12 d postpartum). Cow BW and BCS were taken at six predetermined timepoints throughout the study. Milk samples were collected for component analysis at 7 ± 2 d postpartum and at 55 ± 5 d postpartum. Serial blood samples were analyzed to establish resumption of cyclicity, and ultrasonography was performed at 55 ± 5 d postpartum to evaluate ovarian function. Cows were artificially inseminated at 74 ± 13 d postpartum and turned out with bulls for a 55-d breeding season. Continuous and categorical data were analyzed using the MIXED and GLIMMIX procedures of SAS, respectively. Cow BW and BCS were not different across treatments throughout the study (P≥0.25). Milk fat at 7 d postpartum increased (P=0.05) linearly and total solids tended to increase (P=0.07) as MFP ® increased in the diet; however no other milk components differed as a result of treatment (P≥0.16). No differences in reproductive parameters or calf performance were observed (P≥0.16). These data indicate that supplementation of MFP ® through calving and early lactation may increase milk fat components immediately after calving but does not translate to significant changes in calf growth or dam reproductive performance.